Towards personalizing haemophilia care: using the Haemophilia Severity Score to assess 178 patients in a single institution. (16th July 2013) - Vyas, S.; Enockson, C.; Hernandez, L.; Valentino, L. A.
Summary The phenotypic variability in haemophilia is well documented; however, the biological basis beyond factor VIII and IX activities to explain the differing clinical pictures of the disease remains unclear. It has therefore been of interest to explore other modulators of the disease's variability. Furthermore, a scoring system that reflects the multiple facets of haemophilia symptoms would be useful to compare patients via a comprehensive assessment tool. To this end, Schulman et al., created a measure known as the Haemophilia Severity Score (HSS) as one way to compare phenotypic severity. The aim of this study was to document the differing symptomatology of haemophilia patients using the HSS. Clinical data for 178 haemophilia patients without inhibitors were reviewed and annual incidence of haemarthrosis, orthopaedic joint scores and annual factor usage calculated. Each parameter was then entered into the formula to create the HSS for haemophilia A and B patients with mild, moderate and severe factor deficiencies. Variability in the HSS for patients with the same baseline level of factor was observed for all three deficiency levels and both haemophilia types. In addition, we found that moderate and severe haemophilic B patients tended to have more morbidity based on the above calculations than the haemophilic A counterparts. The HSS is a comprehensive tool that allows for easy numerical comparison of haemophilic patients and elucidates the variable clinical presentation of the disease. The HSS could be used to stratify patients via other possible modulators of haemophilia and discover other aetiologies of the disease.